Literasi Informasi Digital : Sebuah Tantangan bagi Pustakawan - Daryono Daryono (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Information literacy, in addition to being seen as a set of interpersonal competencies, can also be understood from the standpoint of society and human rights. The creativity of librarians in developing and improving services in the digital age is needed to pay attention. Librarians are able to take an active role in taking part in today's emerging technology era by innovating in services. In this era of technology and digital become the trend with slogan